Give the devil his due - Hockensmith, Steve; Falco, Lisa, 1970- (Hockensmith, Steve. Tarot mystery., 2017)
"Reformed con artist-turned-tarot reader Alanis McLachlan gets paid for predicting the future- too bad she didn't see all the trouble in hers. First a figure from her past tries to drag her back into the life of crime she thought she'd left behind. Then a new suitor tries to sweep Alanis off her feet, forcing her on-again, off-again romance with hunky teacher Victor Castellanos to hit the skids. And then there's the little matter of the client who gets an ominous reading from Alanis . . . and is promptly murdered. Danger is in the cards for Alanis, and she'll need all her skill at reading people and reading tarot if she's going to survive."--Amazon.com